El efecto del Product Placement en el aumento del conocimiento de marcas de automóviles - Guzmán Hudtwalcker, Pamela (2021)
In a context in which consumers are overwhelmed with traditional advertising, there are more advertising alternatives that may even be more effective and accepted by consumers. One of them is the Product Placement (PPL), an advertising strategy that refers to the inclusion of a product, brand or company within a movie or a television program, for promotional purposes (D'astous & Chartier, 2000). This advertising strategy is used in various sectors; however, we have decided to analyze its effect only in the automotive industry. This research seeks to identify that the PPL strategy used within this sector generates an increase in brand awareness. Likewise, this paper seeks to prove that this strategy is more effective when the viewers have had a prior positive assessment of the brand in question by the time they notice it in the film. Finally, we will prove if viewers approve this advertising strategy.